The child and adolescent twin study in Sweden (CATSS) - Anckarsäter, H.; Lundström, S.; Kollberg, L.; Kerekes, N.; Palm, C.; Carlström, E.; Långström, N.; Magnusson, P.; Halldner, L.; Bölte, Sven; Gillberg, C.; Gumpert, C.; et al. (Cambridge University Press, 2011)
The Child and Adolescent Twin Study in Sweden (CATSS) is an ongoing longitudinal twin study targeting all twins born in Sweden since July 1, 1992. Since 2004, parents of twins are interviewed regarding the children's somatic and mental health and social environment in connection with their 9th or 12th birthdays (CATSS-9/12). By January 2010, 8,610 parental interviews concerning 17,220 twins had been completed, with an overall response rate of 80%. At age 15 (CATSS-15) and 18 (CATSS-18), twins and parents complete questionnaires that, in addition to assessments of somatic and mental health, include measures of personality development and psychosocial adaptation. Twin pairs in CATSS-9/12 with one or both twins screening positive for autism spectrum disorders, attention deficit/hyperactivity disorder, tic disorders, developmental coordination disorder, learning disorders, oppositional defiant disorder, conduct disorder, obsessive-compulsive disorder, and/or eating problems have been followed with in-depth questionnaires on family, social environment and personality, and subsequently by clinical assessments at age 15 together with randomly selected population controls, including 195 clinically assessed twin pairs from the first 2 year cohorts (CATSS-15/DOGSS). This article describes the cohorts and study groups, data collection, and measures used. Prevalences, distributions, heritability estimates, ages at onset, and sex differences of mental health problems in the CATSS-9/12, that were analyzed and found to be overall comparable to those of other clinical and epidemiological studies. The CATSS study has the potential of answering important questions on the etiology of childhood mental health problems and their role in the development of later adjustment problems.